Research and evaluation of ruts in the asphalt pavement on Lithuanian highways - Sivilevičius, Henrikas; Vansauskas, Vidmantas (Journal of Civil Engineering and Management, 2013)
When exposed to destructive climate and weather factors and heavy vehicle loads, the pavement wears and deflects. In recent decades, apart from cracks and potholes, the depth of ruts grows and makes an increasing share of the pavement surface. The deeper are the tracks, the poorer are traffic conditions for fast-moving cars: drivers are struggling, speed is decreasing and the number of accidents is increasing. After track depth reaches a critical and permissible limit, the road surface must be repaired or speed limit has to be reduced. The work presents a theoretical analysis of track emergence causes and factors determining their depth. With the help of Mobile Road Research Laboratory RST 28, the track depth of all Lithuanian highways has been measured every 20 metres. The obtained data have been processed using the methods of mathematical statistics. Each road has a sample average of every rut, sample standard deviation and a coefficient of individually measured variation. The paper has drawn histograms, calculated skewness, kurtosis and normal distribution and provided lognormal distribution curves of a probability density function. The visualisation and empirical skewness and kurtosis values have revealed that the depth of the rut distributes according to lognormal rather than normal distribution. The average values of the roads having a dividing strip and standard deviations from the distribution across the road have been received. The given dependence of the rut depth of a standard deviation on the averages of rut depth shows an elastic interface of these parameters (determination coefficient R2= 0.741).